Decomposition residual odor volatiles in soil from a West Texas environment - Raymer, Jennifer (Revista Criminalidad, 2020)
Knowledge of decomposition residual odor volatiles can improve cadaver dog training and forensic techniques for victim recovery. The purpose of this study is to characterize decomposition VOCs in soils contaminated with decomposing porcine remains throughout various decomposition phases in an outdoor environment. Both a pig-meat simulation model as well as pig carcasses were used in place of human cadavers, allowed to decompose for three distinctive time periods, 14, 17 and 21 days, and then removed from the deposition site. After removal, the headspace of soil samples, taken from under the cadaver decomposition island (CDI), were analyzed once per week for a period of 4 weeks using solid phase micro extraction- gas chromatography/mass spectrometry (SPME-GC/MS) as the instrumental analysis method. While there have been limited studies in terms of volatile residual odor in soil matrices, it is the goal of this work to further expand the analytical knowledge of residual decomposition odor volatiles by adding another geographical location such as the West Texas region characterized by arid and colder climate conditions. Characterization of VOCs of interest was conducted highlighting trends in abundance and presence as a function of remains contact with soil surface as well as post-remains removal soil collection times.